The Road to a Downstream Emissions Trading System: Designing a Scheme Combining Motorist and Government Participation. (2nd June 2019) - Al-Guthmy, Fahd Mohamed Omar; Yan, Wanglin
Abstract : As downstream road transport has not been fully integrated into any emissions trading scheme, this paper proposes and evaluates the possibility of one by addressing the main barriers hindering its development. Based on this, a scheme which separates the "Cap" and "Trade" participation to motorists and local governments, respectively, is presented through a systematic review. We investigate how the scheme addresses the problems of cost, administrative burden, and fuel allowance allocation as they are all key factors that need equal consideration. We also justify the model's unique structure and characteristics against the world's largest scheme, the European Union Emissions Trading System (EU ETS), to ensure they cater to the three aforementioned issues barring its viability. It is concluded that, by amending specific policy attributes of a road-based emissions trading scheme significantly, it could be more practical both economically and administratively. Also, leveraging on existing institutional arrangements would allow for an economically feasible environment for the administration and management of such a scheme.